(untitled) (Linguostylistic Studies, 2021)
The article examines the works of Volynian poets dedicated to Lesya Ukrainka, actually, those of them that are not conventional dedications but are the poem-dedications that model her image, primarily via various associative-semantic connections with the poetess’ personality and creativity. Less often, the authors in their dedications resort to projections on the toponymy directly connected with L.Ukrainka, in particular, such as Volyn, Kolodyazhne, Voloshky, Chekno, Yalta (works by V. Hei, N. Horyk, N. Humeniuk, V. Lazaruk, L. Lezhanska, J. Strutsiuk), involving also the event dimension of her biography – a children’s council in the castle of Lubart (N. Humeniuk), participation in the activities of "Pleiades" (J. Strutsiuk). The study focuses on detecting figurative, functional, stylistic, and syntactical means of modeling the image of Lesya Ukrainka in poetic dedications, with a clear differentiation of age parameters (portraits of Lesya-child, Lesya-adolescent, and Lesya-adult person). The authors of the article identified and analyzed the most productive of them - paraphrases, among which are those that belong to the individually-expressive, such as fortune teller (O. Bogachuk), a tear of Taras’ fate (V. Hei), prophet, voice, hope, genius (N. Humeniuk), metaphors and comparative structures, which verbalize mainly her inner world and determinative traits of character – courage, resilience, steadfastness in defending national interests and the native language. The study has revealed the frequency of modeling Lesya Ukrainka's image with the help of associative actualizations and semantic correlations with the characters of her works – mostly with Mavka and Kassandra (O. Bogachuk, N. Horyk, Y. Silchuk). Numerous explications of the pseudonym Ukrainka as a dominant evaluative element in contexts that reveal her inherent and inexhaustible role in the development of the Ukrainian national-linguistic and spiritual space can also be considered as typical. Dedication poems form separate cycles of the works of many Volyn poets (V. Hei, V. Lazaruk, J. Strutsiuk). In the texts of some dedications, there are epigraphs-quotations from the works of Lesya Ukrainka (R. Bratun’, N. Humeniuk, O. Kryshtalska).